Alterations of brain volumes in women with early life maltreatment and their associations with oxytocin - Mielke, Emilia Louisa L.; Neukel, Corinne; Bertsch, Katja; Reck, Corinna; Herpertz, Sabine (Hormones and behavior, 2018)
Early life maltreatment (ELM) is associated with different neurobiological alterations. Lower oxytocin and altered grey matter volumes (GMV) in brain regions associated with the central oxytocin system, such as the hypothalamus, amygdala, and nucleus accumbens, have been reported in women with ELM. However, the association between peripheral oxytocin and brain morphometry in women with ELM has not been studied yet. We therefore collected blood samples from 33 women with and 25 women without ELM, all without current mental disorders to measure and compare oxytocin levels between the two groups. Furthermore, T1-weighted high-resolution structural magnetic resonance brain images of a subsample of these women were collected, analyzed with voxel-based morphometry, compared between the two groups, and correlated with oxytocin levels. There were no differences in oxytocin levels between the groups. However, oxytocin levels were associated with different brain regions in women with ELM compared with control women without ELM: A positive association between GMV in the nucleus accumbens and oxytocin was specific for control women but not for women with ELM. For the hypothalamus, there was a positive association between GMV and oxytocin in control women. However, the same region was negatively associated with oxytocin in women with ELM and it showed larger GMV compared to control women without ELM. For the amygdala, a negative association between GMV and oxytocin was specific for women with ELM. Results are discussed with regard to previous research on endocrine and neurostructural alterations in individuals with ELM.